AI-Driven Teacher Development: Digital-Age Mentorship and Professional Training Models - Kulkarni, Radhika; Raut, Tejas; Kolhe, Vinayak (Journal of Educational Research and Policies, 2025)
Artificial Intelligence (AI) is increasingly influencing teacher training by enabling dynamic mentorship and ongoing professional development. This study explored how trainee and in-service teachers in Jamaica use AI tools to enhance pedagogical and technological skills, while promoting continuous learning. Through a mixed-methods approach involving 40 participants, comprising teacher-educators, cooperating teachers, and trainee and in-service teachers. The study examined perceptions of AI-driven mentorship, skill-building, and access to professional learning. The data was collected using interviews, questionnaires, and focus group discussions. Results suggest positive responses among trainee teachers, with tools like ChatGPT and Grammarly being widely adopted. However, challenges remain around ethical concerns, digital literacy, and equitable access. The findings highlight the potential of AI to support teacher training while emphasizing the need for inclusive training programs.